Participation in international robotics competitions as a new form of student travel - Wieczorek, Luiza; Piech, Wiktor; Cybulski, Bartłomiej; Kujawiński, Mateusz; Węgierska, Agnieszka (Turyzm/Tourism, 2018)
The article presents opportunities for foreign travel by students based on trips to international competitions, in particular robotic competitions. As the data collected show, these have attracted several thousand participants in recent years. The article presents an additional effect of participation in such competitions which is tourism during the trips.